2021
DOI: 10.1029/2021tc006853
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Non‐Optimally Orientated Faults Due to Glacially Induced Stresses

Abstract: The deformation due to an ice load is accompanied by displacement and stress changes. These stress changes are known to have created large‐magnitude earthquakes along pre‐existing faults during and after deglaciation of the Late Quaternary ice sheets. However, these so‐called glacially induced faults have been found to be not optimally orientated in their respective regional stress regime. Here, we analyzed the potential of non‐optimally orientated fault reactivation within a glacially induced stress field as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 76 publications
(143 reference statements)
0
8
0
Order By: Relevance
“…The expected stress drop in our models can be estimated to first order as (1 – λ f ) σ n ʹ( μ s – μ d ) R 0 (Ulrich, Gabriel, Ampuero, & Xu, 2019) which in model 4, for example, increases from 0 MPa at the surface to 24 MPa at 15 km depth. Thus, both the dynamically modeled stress drop and the rupture velocity could be decreased in models with lower R 0 ; however, low R 0 would hinder rupture nucleation on any segment and would imply that even well‐oriented parts of the fault are stressed far from criticality, which is at odds with observations from continental drilling (e.g., M. D. Zoback & Townend, 2001; Townend & Zoback, 2000) and post‐glacial fault reactivation (e.g., Steffen & Steffen, 2021) that indicate the crust is critically stressed (e.g., M. L. Zoback & Zoback, 2007). Sibson (1990) distinguished two classes of misoriented faults: those that are unfavorably oriented under Anderson‐Byerlee conditions, and those that are severely misoriented and require pore fluid pressures to exceed σ 3 for the fault to remain mechanically viable, breaching the so‐called “hydrofrac limit” (e.g., Abers, 2009) at which deformation proceeds via the opening of new hydrofractures rather than continued fault slip.…”
Section: Discussionmentioning
confidence: 97%
“…The expected stress drop in our models can be estimated to first order as (1 – λ f ) σ n ʹ( μ s – μ d ) R 0 (Ulrich, Gabriel, Ampuero, & Xu, 2019) which in model 4, for example, increases from 0 MPa at the surface to 24 MPa at 15 km depth. Thus, both the dynamically modeled stress drop and the rupture velocity could be decreased in models with lower R 0 ; however, low R 0 would hinder rupture nucleation on any segment and would imply that even well‐oriented parts of the fault are stressed far from criticality, which is at odds with observations from continental drilling (e.g., M. D. Zoback & Townend, 2001; Townend & Zoback, 2000) and post‐glacial fault reactivation (e.g., Steffen & Steffen, 2021) that indicate the crust is critically stressed (e.g., M. L. Zoback & Zoback, 2007). Sibson (1990) distinguished two classes of misoriented faults: those that are unfavorably oriented under Anderson‐Byerlee conditions, and those that are severely misoriented and require pore fluid pressures to exceed σ 3 for the fault to remain mechanically viable, breaching the so‐called “hydrofrac limit” (e.g., Abers, 2009) at which deformation proceeds via the opening of new hydrofractures rather than continued fault slip.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, the Carlsberg Fault Zone strikes almost NW–SE and thus, has a different orientation than the east–west‐striking LFS. However, this does not necessarily contradict a glacially induced reactivation of both fault systems as recent modelling results have shown that faults do not have to be optimally oriented to be reactivated by glacially induced stress (Steffen & Steffen 2021).…”
Section: Interpretation and Discussionmentioning
confidence: 97%
“…In general, modelling results suggest that stress from glacial isostatic adjustments can reactivate pre‐existing faults in a thrust, strike‐slip or normal stress regime and indicate that reactivation is largely dependent on the location of the fault to the ice sheet and the current stress ratio (Steffen & Steffen 2021). During the maximum extent of all three major Pleistocene glaciations, our study area was fully covered by ice sheets (e.g.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Stress changes induced by GIA can reach more than ten MPa near, and in the forebulge of, the continental ice-sheet load zones (Figure 6), reaching deep into the lithosphere (e.g., Wu and Johnston, 2000;Wu et al, 2021;Vachon et al, 2022). As these stress changes can reach the range of typical earthquake stress drops, they are capable of triggering earthquakes on faults suitably oriented with respect to the induced stress field, or arrest slip on unfavorably oriented faults (e.g., Steffen and Steffen, 2021). Large prehistoric earthquake ruptures and current seismicity in Scandinavia, Greenland, North America, the European Alps, and around Antarctica have been linked to these large and enduring climate-driven stress changes (e.g., Wu and Johnston, 2000;Ivins, 2003;Steffen et al, 2020;Steffen et al, 2021;Wu et al, 2021;Vachon et al, 2022, and references therein).…”
Section: Ice Age Climate Cyclesmentioning
confidence: 99%
“…As these stress changes can reach the range of typical earthquake stress drops, they are capable of triggering earthquakes on faults suitably oriented with respect to the induced stress field, or arrest slip on unfavorably oriented faults (e.g., Steffen and Steffen, 2021). Large prehistoric earthquake ruptures and current seismicity in Scandinavia, Greenland, North America, the European Alps, and around Antarctica have been linked to these large and enduring climate-driven stress changes (e.g., Wu and Johnston, 2000;Ivins, 2003;Steffen et al, 2020;Steffen et al, 2021;Wu et al, 2021;Vachon et al, 2022, and references therein). In the near field, triggered earthquake activity likely was most intense during and shortly after the latest pulse of deglaciation (e.g., Figure 6B), but enhanced seismicity in the previously glaciated areas appears to continue into the present, both in North America and Fennoscandia (Figure 6E).…”
Section: Ice Age Climate Cyclesmentioning
confidence: 99%